OCTOPUS‐LIKE 2, a novel player in Arabidopsis root and vascular development, reveals a key role for OCTOPUS family genes in root metaphloem sieve tube differentiation. Issue 4 (6th September 2017) - Ruiz Sola, M. Aguila; Coiro, Mario; Crivelli, Simona; Zeeman, Samuel C.; Schmidt Kjølner Hansen, Signe; Truernit, Elisabeth
Summary: Protophloem and metaphloem sieve tubes are essential for transporting carbohydrates and signalling molecules towards sink tissues. OCTOPUS ( OPS ) was previously identified as an important regulator of protophloem differentiation in Arabidopsis roots. Here, we investigated the role of OCTOPUS‐LIKE 2 ( OPL2 ), a gene homologous to OPS . OPL2 expression patterns were analysed, and functional equivalence of OPS and OPL2 was tested. Mutant and double mutant phenotypes were investigated. OPS and OPL2 displayed overlapping expression patterns and a high degree of functional overlap. A mutation in OPL2 revealed redundant functions of OPS and OPL2 in developmental processes in which OPS was known to play a role, notably cotyledon vascular patterning and protophloem development. Moreover, we also uncovered redundant roles for OPS and OPL2 in leaf vascular patterning and, most interestingly, metaphloem sieve tube differentiation. Our results reveal a novel OPS‐like protein that, together with OPS, is an important regulator of vascular patterning, root growth and phloem development. OPS and OPL2 are the first genes identified that play a role in metaphloem sieve tube differentiation.